2009
DOI: 10.1007/s10585-009-9257-8
|View full text |Cite
|
Sign up to set email alerts
|

Early incorporated endothelial cells as origin of metastatic tumor vasculogenesis

Abstract: Vascularization of solid tumors is thought to occur by sprouting or intussusceptive angiogenesis, co-option of existing vessels, and vasculogenic mimicry after the onset of tumor hypoxia, when the tumor radius exceeds the oxygen diffusion distance. In contrast, here we show that individual endothelial cells that are incorporated into pre-hypoxic tumors give rise to tumor blood vessels via vasculogenesis. Small metastatic lung tumor sections obtained after tail-vein injection of a syngeneic breast cancer cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The presence of tumor cell‐lined channels provides a potential additional route by which metastases may escape from a tumor or a lymph node into the blood stream. It has been suggested that the blood vessels in the sites of metastatic growth are being formed from within the tumor utilizing occasional EC incorporated into the tumor [10]. Therefore, the first blood vessels in metastases would be composite ones formed by both tumor and an EC.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of tumor cell‐lined channels provides a potential additional route by which metastases may escape from a tumor or a lymph node into the blood stream. It has been suggested that the blood vessels in the sites of metastatic growth are being formed from within the tumor utilizing occasional EC incorporated into the tumor [10]. Therefore, the first blood vessels in metastases would be composite ones formed by both tumor and an EC.…”
Section: Discussionmentioning
confidence: 99%
“…VM has been detected in melanoma, breast carcinoma, prostate carcinoma, ovarian carcinoma, astrocytoma, and Ewing sarcoma, etc (Shirakawa et al, 2002;Yue and Chen, 2005;Elzarrad et al, 2009). Microarray analysis indicates that VM-positive tumor cells of aggressive melanoma displayed elevated levels of genes associated with undifferentiated embryonic-like phenotype (Hendrix et al, 2003a).…”
Section: Current Understanding Of Tumor Vmmentioning
confidence: 99%
“…Endothelial cells (EC) are key mediators of vasculogenesis during development and angiogenesis during the pathogenesis of ischemic cardiovascular diseases and cancer (Poole et al, 2001; Landmesser et al, 2004; Willerson and Ridker, 2004; Elzarrad et al, 2009). They also play a central role in general organogenesis (Levenberg et al, 2007), making them an important tool for tissue engineering and for studying the mechanisms involved in the pathogenesis of different forms of vascular diseases, cancer and diabetes.…”
Section: Introductionmentioning
confidence: 99%